Managing women’s matter: a cross-cultural study of doctor-patient relationship in Pakistan and Malaysia - Rehman, Adeela; Mohamad Diah, Nurazzura (IIUM Press, International Islamic University Malaysia, 2020)
Healthcare providers in the Muslim community take their profession as an obligation to serve the patients and community in humanistic way, that is described by the Islamic Law. The present study focuses on the doctorpatient relationship in two Muslim countries; Pakistan and Malaysia, to explore the ethical practices in the health profession. The study comprises of cross-sectional qualitative research design in which, in-depth interviews were conducted from female doctors and patients. Data was collected from female patients by visiting the clinics and hospitals for their concerns related to health. Sample of ten female patients and ten doctors (five from each country) were selected for the study. The findings highlighted the moderate relationship of doctors with patients and vice-versa. In Pakistan, majority of the doctors mentioned professional behaviors with the patients, as maternal healthcare is very sensitive and critical in nature. During their medical trainings, although they learnt professional ethics based on Islamic values and integrity however power of doctors over patients has been reported. Interestingly, most women who attended the menopause clinic in Malaysia accepted the doctor’s dominance, because doctors talk to them about their problems and the women tend to accept their expertise. In conclusion, doctors in Pakistan and Malaysia have tried their level best to follow the professional ethics to treat the patients well. Doctors and patients need to realize each others perimeter in a larger setup and try to establish reciprocal relationship with one another.